The Correlation between Students’ Mastery of Vocabulary and Their Speaking Skill - Siti Khairani; Dinovia Fannil Kher (Universitas Negeri Padang, 2023)
This correlational study investigates the correlation between eleventh-grade students' vocabulary mastery and speaking skills at SMAN 1 Kec Payakumbuh. The primary objectives include evaluating vocabulary and speaking skill levels and determining their relationship. This research aims to enhance practical and theoretical aspects of speaking activities. The researcher employed a quantitative method using Pearson’s correlation to measure the relationship between two variables: students' vocabulary mastery (independent variable, X) and their speaking ability (dependent variable, Y). The study population includes all 11th graders at SMAN 1 Kec Payakumbuh for the academic year 2021/2022, totalling 160 students. A sample of 31 students from class XI IPA 3 was selected. Tests for speaking ability and vocabulary mastery were conducted to assess the relationship between the variables. The findings of this study demonstrated a connection — one that was validated by statistical examination of the data — between the students'' vocabulary knowledge and their ability to communicate verbally. It was revealed that there is a substantial association between the vocabulary knowledge of students in the eleventh grade at SMA N 1 Kec Payakumbuh and their speaking ability. The research reveals a positive correlation, indicating that improved vocabulary is linked to better speaking abilities. Statistical analysis supports this, with a significant p-value below 0.05, validating the hypothesis.